Faraday rotation maps of disc galaxies - Pakmor, Rüdiger; Guillet, Thomas; Grand, Robert J. J.; Springel, Volker (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. Faraday rotation is one of the most widely used observables to infer the strength and configuration of the magnetic field in the ionized gas of the M
Gesehen am 23.01.2019